Omega-3 phospholipids and obesity-associated NAFLD: Potential mechanisms and therapeutic perspectives - Mitrovic, Marko; Sistilli, Gabriella; Horakova, Olga; Rossmeisl, Martin (European journal of clinical investigation, 2022)
Prevalence of non-alcoholic fatty liver disease (NAFLD) increases in line with obesity and type 2 diabetes, and there is no approved drug therapy. Polyunsaturated fatty acids of n-3 series (omega-3) are known for their hypolipidaemic and anti-inflammatory effects. Existing clinical trials suggest varying effectiveness of triacylglycerol- or ethyl ester-bound omega-3 in the treatment of NAFLD, without affecting advanced stages such as non-alcoholic steatohepatitis. Preclinical studies suggest that the lipid class used to supplement omega-3 may determine the extent and nature of their effects on metabolism. Phospholipids of marine origin represent an alternative source of omega-3. The aim of this review is to summarise the available evidence on the use of omega-3 phospholipids, primarily in obesity-related NAFLD, and to outline perspectives of their use in the prevention/treatment of NAFLD. A PubMed literature search was conducted in May 2021. In total, 1088 articles were identified, but based on selection criteria, 38 original papers were included in the review. Selected articles describing the potential mechanisms of action of omega-3 phospholipids have also been included. Preclinical evidence clearly indicates that omega-3 phospholipids have strong antisteatotic effects in the liver, which are stronger compared to omega-3 administered as triacylglycerols. Multiple mechanisms are likely involved in the overall antisteatotic effects, involving not only the liver but also adipose tissue and the gut. Robust preclinical evidence for strong antisteatotic effects of omega-3 phospholipids in the liver should be confirmed in clinical trials. Further research is needed on the possible effects of omega-3 phospholipids on advanced NAFLD.
Keywords: Non-alcoholic Fatty Liver Disease; Obesity; Fatty Acids, Omega-3; omega-3 mastné kyseliny; marine phospholipids; lidé; fosfolipidy; obezita; obesity; Phospholipids; nealkoholová steatóza jater; n-3 polyunsaturated fatty acids; non-alcoholic fatty liver disease; krill oil; Humans